2001
DOI: 10.1302/0301-620x.83b6.9726
|View full text |Cite
|
Sign up to set email alerts
|

Changes in proximal femoral strain after insertion of uncemented standard and customised femoral stems

Abstract: We have compared the changes in the pattern of the principal strains in the proximal femur after insertion of eight uncemented anatomical stems and eight customised stems in human cadaver femora. During testing we aimed to reproduce the physiological loads on the proximal femur and to simulate single-leg stance and stair-climbing. The strains in the intact femora were measured and there were no significant differences in principal tensile and compressive strains in the left and right femora of each pair. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 29 publications
2
45
0
1
Order By: Relevance
“…Our findings correspond to the results reported by other authors [5, 18, 19]. However, strain studies on the external cortex have been used uncritically to predict the in vivo performance, as the stress at the internal interface between the implant and endosteal bone never has been studied.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings correspond to the results reported by other authors [5, 18, 19]. However, strain studies on the external cortex have been used uncritically to predict the in vivo performance, as the stress at the internal interface between the implant and endosteal bone never has been studied.…”
Section: Discussionsupporting
confidence: 90%
“…Much work has been done to obtain a design of the stem that maintains physiological strain after insertion of the implant [5, 18-20]. Strain gauge measurements usually have been employed to study the pattern of load transfer from the stem to the femur after insertion of a prosthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,8,10,23,24 These studies uniformly revealed a dramatic reduction of the principal strains in the proximal part of the femur for both stem types with the greatest decreases at the calcar especially for the standard stems. Customised proximal fit stems and traditional stems all display non-physiological strain patterns within the proximal femur, with slightly more physiological patterns for the customised stems.…”
Section: Discussionmentioning
confidence: 83%